Cytoplasmic and Nuclear Localization of TCTP in Normal and Cancer Cells - Yu-Ping Ma; Wu-Ling Zhu (Biochemistry Research International)
Objective. Intracellular localization of translationally controlled tumour protein (TCTP) was investigated in cancer cells. Methods. The expression and localization of TCTP were detected at 12 h, 24 h, 48 h, 60 h time points in culture of human hepatocarcinoma cell line HepG2, human cervical carcinoma cell line HeLa, and human normal liver cell line HL-7702 by immunofluorescence. Results. TCTP was expressed in both normal and tumor cells, and its localization changes at different time points. TCTP was mainly expressed in cytoplasm from 24 h to 48 h then expressed in both nucleus and cytoplasm at 60 h in HL-7702 cells. While in HepG2 cells, TCTP first localized at cell membrane within 24 h then at both nucleus and cytoplasm from 48 h to 60 h; TCTP localized at both nucleus and cytoplasm from 12 h to 60 h in Hela cells. Conclusion. The translocation of intracellular expression of TCTP in normal and tumor cells at different time points may pave a path to the studying of TCTP role in tumor growth.